Blended Learning Praxis in Delivery of Teacher Development Programmes: A review - Danushka, S.A.N. (Faculty of Management Studies and Commerce University of Sri Jayewardenepura, 2024)
Blended learning is widely accepted as an effective mode of course delivery in higher education. As it has been pragmatically tested to see the effectiveness in the delivery of professional courses, the use of blended learning in the delivery of teacher development programmes needs an inquiry into empirical literature to see the applicability. The review was set with three questions, identifying appropriate instructional strategies for blended learning, finding instructional strategies and activities employable for blended teacher development programmes and deciding the appropriate blended learning model for teacher development programme delivery. Review articles were searched via five online databases (Google Scholar, ScienceDirect, scinapse, ERIC and ProQuest) and paper selection criteria guided to select of sixty-three papers from peer-reviewed journals. Thematic review findings show that self-directed learning, self-regulated learning and self-paced learning strategies are commonly used in both general and blended teacher development programmes. Self-directed learning strategy has been the preference in the delivery of blended teacher development programmes. Asynchronous forum discussions, providing self-reflective materials and group activities are highly preferred in blended teacher development programmes. The flipped classroom model is preferred in blended teacher development programmes as it facilitates to improvement of teacher professional skills with the presence of peers and mentors.
Keywords: Blended learning, Teacher development programmes, Instructional strategies, Instructional activities, Flipped classroom